(3UdI GdUdIs - (3GHf GdRHjQ , CHh LYaQ CMeO Hf EHQGgje GdCfOdSj GdZQfGWj, GHf GdRfjQ GdKbaj,J (B708 (3g` s
(3ChdgG (B:s
(3ef Chd GSe eMeO s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3hGdehLhO efg (B: (3GdfUa GdKGfi ef Chd GSe (B" (3eMeO (B" (3Edi BNQ GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B138s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B93 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B850) s
Keywords: (3GdJGQjNs